Antenna transfer function evaluation scheme for ultra wideband medical applications - Koonchiang, Krisada; Manositthichai, Narongsak; Fongsamut, Chalermpan; Promwong, Sathaporn (My University, 2011)
Antennas which are used to transmit and receive UWB signals must be able to accomodate its large bandwidth. Moreover, the signals should not be distorted too much when they pass through the antennas. Therefore, the transfer function of antennas should be known for the performance evaluation. Conventionally, the authors measure the transfer function of the antenna by measuring the transmission coefficient between the transmit and the receive antenna, assuming that the transmit and receive antennas are identical. In this presentation, a more accurate three-antenna method is introduced so that the transfer function of each individual antenna can be measured. By using this method, biconical antennas are tested. The results show that these transfer functions are close to each other and that the antenna can be used for UWB meadical application (UWB-MA). Friis' transmission formula in complex form to treat the UWB signals to take into account the waveform distortion due to the frequency characteristics of the antennas [1], [7]. It is noted that Friis' transmission formula is applicable only in the far field region. In wireless meadical environments, however, the distance may not satisfy the far field condition. In this paper, we discusses the antenna evaluation of the transmission properties in Fresnel region. © 2011 IEEE.
Keywords: Friis' transmission formula; inpulse radio; medical application; UWB; UWB antennas